2017
DOI: 10.1021/jacs.6b11875
|View full text |Cite
|
Sign up to set email alerts
|

Doping-Induced Anisotropic Self-Assembly of Silver Icosahedra in [Pt2Ag23Cl7(PPh3)10] Nanoclusters

Abstract: Atomically precise self-assembled architectures of noble metals with unique surface structures are necessary for prospective applications. However, the synthesis of such structures based on silver is challenging because of their instability. In this work, by developing a selective and controlled doping strategy, we synthesized and characterized a rod-shaped, charge-neutral, diplatinum-doped Ag nanocluster (NC) of [PtAgCl(PPh)]. Its crystal structure revealed the self-assembly of two Pt-centered Ag icosahedra t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 42 publications
4
92
0
Order By: Relevance
“…prepared a Pt‐doped [PtAg 24 (SR) 18 ] 2− cluster, whose structure can be described as a centered icosahedral core Pt@Ag 12 stabilized by six distorted dimeric staple ‐RS‐Ag‐SR‐Ag‐SR‐ motifs, which was not observed in un‐doped Ag nanoclusters; Bakr et al. determined the structure of an anisotropic Pt‐doped [Pt 2 Ag 23 Cl 7 (PPh 3 ) 10 ] nanocluster, but the structure of its parental hydride‐rich [Ag 18 H 16 (PPh 3 ) 10 ] 2+ cluster remains unclear due to its instability …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…prepared a Pt‐doped [PtAg 24 (SR) 18 ] 2− cluster, whose structure can be described as a centered icosahedral core Pt@Ag 12 stabilized by six distorted dimeric staple ‐RS‐Ag‐SR‐Ag‐SR‐ motifs, which was not observed in un‐doped Ag nanoclusters; Bakr et al. determined the structure of an anisotropic Pt‐doped [Pt 2 Ag 23 Cl 7 (PPh 3 ) 10 ] nanocluster, but the structure of its parental hydride‐rich [Ag 18 H 16 (PPh 3 ) 10 ] 2+ cluster remains unclear due to its instability …”
Section: Figurementioning
confidence: 99%
“…According to the superatom theory, the number of free valence s‐electrons in 1 was calculated to be 8 (note that Pt acts as a closed d‐shell d 10 s 0 element as a dopant instead of d 9 s 1 as in the free atom), which is a magic number, explaining the formation and stability of the cluster. To investigate the stability of the superatom nanocluster, we measured the UV‐vis spectrum of 1 in solution form in the dark.…”
Section: Figurementioning
confidence: 99%
“…This result illustrated that the valence state of Ag in the Pt 1 Ag 9 nanocluster lies between 0 and +1. The Pt 4f 7/ 2 binding energy in the Pt 1 Ag 9 nanocluster was determined by XPS as 71.2 eV, which corresponds to Pt (0) (71.2 eV, Figure c, d) , . The left expected elements (P, Cl, F and C) are also found in the X‐ray photoelectron spectroscopy, details are in the supporting information (Figure S3).…”
Section: Resultsmentioning
confidence: 98%
“…Upon analysis of the monodisperse final product, the atomic level understanding of structure‐related properties can be thus achieved. Nowadays, icosahedral structured Pt 1 Ag 12 nanoclusters and series of its assembled super‐molecular nanoclusters have been synthesized and structurally determined, which deepened the systematic study of the fluorescence properties of this type of nanoclusters . Zhu group reported that disassembling an assembled nanocluster with icosahedral units may lead the emission ranges to lower field.…”
Section: Introductionmentioning
confidence: 99%
“…The full structure of 1 is shown in Figures 1 A and B, from which it can be clearly seen that the cluster comprises 5 Pt atoms, 22 Ag atoms, and 32 alkynyl groups. Two composition features are present in this cluster: first, compared with Pt‐doped Ag NCs, for example, Pt 2 Ag 23 Cl 7 (PPh 3 ) 10 (2) and [PtAg 24 (2,4‐SPhCl 2 ) 18 ] 2− (3) , [ 29] the five Pt atoms in cluster 1 show no obvious center preference, which is in sharp contrast with the Pt acting as the icosahedral center in 2 and 3 , indicating the unique effect of alkynyl on the site selectivity of Pt atoms. Then, the cluster contains 27 metal atoms, which is quite rare in alkynyl‐stabilized platinum‐silver complexes or clusters …”
Section: Figurementioning
confidence: 99%